Pengaruh Penerapan Model Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Teorema Pythagoras Pada Siswa Kelas VIII SMPN 1 Suralaga Tahun Ajaran 2023/2024 - aini, rohmiatun; Sripatmi; Salsabila, Nilza Humaira; Baidowi, Baidowi (Mandalika Mathematics and Educations Journal, 2024)
This study aims to determine the effect of problem-based learning models on students' Pythagorean theorem problem solving ability. This research was carried out at SMPN 1 Suralaga for the 2023/2024 school year. The type of research used is a quasi experiment. The population in this study were class VIII students of SMPN 1 Suralaga for the 2023/2024 academic year. The sample was 44 students consisting of 22 experimental class students and 22 control class students. The data collection techniques used are observation and tests. While the research instrument consists of observation sheets, problem-solving ability test sheets, lesson implementation plans and student worksheet. Data taken with t-test, obtained acceptable results    accepted, there is a difference in the problem-solving ability of the Pythagorean theorem in students whose learning used the problem-based learning model with students who used the direct learning model. The average posttest result for the experimental class was higher than the control class, namely 82.41>75,00.  This shows that there is an influence of the problem based learning model on the Pythagorean theorem problem solving abilities of class VIII students at SMPN 1 Suralaga using the effect size test, obtained d=0.67, which means the influence given is in the medium category.